2023
DOI: 10.1097/anc.0000000000001071
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Mothers of Preterm Infants in the Neonatal Intensive Care Unit During the COVID-19 Pandemic

Abstract: Background: The neonatal intensive care unit (NICU) stay following the birth of a preterm infant can be stressful and traumatic for families. During the COVID-19 pandemic, the NICU environment changed precipitously as infection control and visitor restriction measures were implemented. Purpose: Our study aimed to examine the impact of the pandemic policies on the experiences of mothers of preterm infants during their stay in the NICU. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Our findings also highlight a lower interaction between extremely preterm newborns and their parents. A previously published study described that, during the stay in the NICU, mothers of preterm infants experienced the disruption of family dynamics, support and bonding, physical and emotional isolation, a negative psychological impact compounded by increased concerns, a change in maternal role, and survival mode mentality [ 34 ]. A meta-analysis including 38 studies and a total of 3025 parents of preterm infants indicated that parents of preterm-born children experienced only slightly more stress than parents of term-born children.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also highlight a lower interaction between extremely preterm newborns and their parents. A previously published study described that, during the stay in the NICU, mothers of preterm infants experienced the disruption of family dynamics, support and bonding, physical and emotional isolation, a negative psychological impact compounded by increased concerns, a change in maternal role, and survival mode mentality [ 34 ]. A meta-analysis including 38 studies and a total of 3025 parents of preterm infants indicated that parents of preterm-born children experienced only slightly more stress than parents of term-born children.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also highlighted a lower interaction between extremely preterm newborns and their parents. A previously published study described that during the stay in the NICU, mothers of preterm infants experienced disruption of family dynamics, support and bonding; physical and emotional isolation; negative psychological impact compounded by increased concerns, change in maternal role and survival mode mentality [25]. Furthermore, the complex psychosocial needs of parents of extremely preterm infants were challenging for the NICU and its staff already before the COVID-19 pandemic [26].…”
Section: Discussionmentioning
confidence: 99%
“…Однако стоит отметить, что значительно меньше исследований посвящено вопросам психического здоровья женщины в ситуации преждевременных родов и рождения недоношенного ребенка. Преждевременное завершение беременности и высокие риски для жизни и здоровья ребенка являются значительным стрессом для матери, негативно отражающимся на ее эмоциональном состоянии [16,18].…”
unclassified